(untitled) (ENTHYMEMA, 2024)
Roman Jakobson (1896-1982) is not currently a highly cited author in the field of literary studies. Along with other inescapable names of the heyday of structuralism, he has fallen into relative oblivion. Although he undoubtedly continues to be recognized as one of the giants of the Human Sciences during the 20th century, his theoretical conceptions and methodological proposals find limited applicability and have been subjected to severe objections by leading contemporary scholars. However, there is ground to believe that this neglect arises from the fact that his entire output has been reduced to the essentialist positions of his later North American period. In this paper, we contend that Jakobson´s ideas belonging to the earlier periods of Russian formalism and Czech structuralism have been all to often overlooked, and might have a revitalizing and stimulating impact on contemporary disciplinary discussions.